Application of the Six Sigma methodology in the evaluation of the results in Blood Cell Count EQAS Program (PNAEQ) - Ovelheiro, Ana Raquel (2019)
The hemogram is one of the most frequently requested laboratory tests, in hospital and ambulatory. It is important in the evaluation of anemia, polycythemia, leukemia, infection, inflammation, among others. The main objective of this work was to evaluate the Sigma quality level of the clinical laboratories participating in PNAEQ’s EQA Blood Cell Count program (2015-2017) referring to the parameters hemoglobin, platelets, leukocytes and erythrocytes. For this study, Six Sigma was used as methodology and metrics, supported by the application of the DMAIC (Define, Measure, Analyze, Improve, Control) cycle.